Empowering safety with the SAFEME-Girls Safety Kit / Dr. Siti Syairah Mohd Mutalip, Dr. Ruzianisra Mohamed and Dr. Gurmeet Kaur Surindar Singh - Mohd Mutalip, Siti Syairah; Mohamed, Ruzianisra; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The 'SAFEME-Girls Safety Kit' programme, held at Sekolah Menengah Kebangsaan (SMK) Saujana Utama, Selangor, served as an integral component of the community service and student development initiative. Organised by the Faculty of Pharmacy, UiTM Puncak Alam Campus, this momentous event, which took place on September 14, 2023, marked yet another noteworthy milestone. The programme successfully engaged 100 female students, aged 15-16, providing them with invaluable knowledge on the appropriate utilisation of the recently developed safety kit. To ensure a comprehensive learning experience, the programme enlisted the expertise of four lecturers and four internship students from the Faculty of Pharmacy, along with a lecturer from the Faculty of Sport Science and Recreation, who skilfully served as speakers and facilitators. The SAFEME-Girls Safety Kit stands as a remarkable testament to innovation, comprising essential safety provisions such as a torchlight, whistle, alarm, pepper spray, emergency contact numbers, and an instructive infographic outlining basic self-defence techniques. This meticulously crafted kit has garnered recognition in esteemed innovation competitions, including the Pharmacy Invention, Innovation, and Design Exhibition (Pharm-IIDEx) 2022, the UiTM Invention, Innovation, and Design Exhibition (IIDEx) 2022, and the International Virtual Expo of Innovation Product and System Design (INVIDE) 2023, where it secured gold and bronze awards.